Performance effectiveness of technology dissemination system of state department of agriculture in Kerala and Andhra Pradesh: a comparative analysis - Modem Ravikishore (Department of Agricultural Extension College of Agriculture, 2018)
The present study entitled ‘Performance effectiveness of technology dissemination system of State Department of Agriculture in Kerala and Andhra Pradesh: A comparative analysis’ was conducted in Kerala and Andhra Pradesh states during 2014-2017 covering 200 extension professionals and 100 farmers form both the states with equal proportions. Agricultural extension workers of State Department of Agriculture are personnel who are responsible for meeting the goals of extension system. Evaluation of the success of extension delivery programmes, in most cases, has focused on performance effectiveness of extension personnel of State Department of Agriculture. However, the effectiveness and efficiency with which extension personnel deliver extension services cannot be over looked as this may in fact be a greater reason for success or failure of extension programmes. This necessitates the present study with the objective of assessing and comparing performance effectiveness of State Department of Agriculture in Kerala and Andhra Pradesh vis-a-vis technology dissemination system. Comparative analysis of technology dissemination systems of Kerala and Andhra Pradesh would allow inter-scalability of technologies. The findings demonstrated that most of the extension professionals with respect to Kerala as well as Andhra Pradesh states have moderately favorable attitudes towards technology dissemination system of State Department of Agriculture (SDA). Comparative analysis of attitude among Kerala and Andhra Pradesh extension personnel have shown that there was significant difference towards State Department of Agriculture. Attitude of Kerala extension professionals was influenced by the factors age, experience, training and organizational commitment. Attitude of Andhra Pradesh extension personnel was influenced by the factors training, organizational commitment, perceived workload, job satisfaction and achievement motivation. Performance effectiveness index of technology dissemination system of State Department of Agriculture (SDA) was devised and measured in three components namely: Human effectiveness component, Dissemination system component and Organisational effectiveness component and the results revealed that majority of the extension personnel with respect to Kerala as well as Andhra Pradesh, performance effectiveness index was medium. Comparative analysis of Performance effectiveness index of technology dissemination system of State Department of Agriculture (SDA) among Kerala and Andhra Pradesh extension personnel have shown that there was significant difference. Performance effectiveness index of Kerala extension professionals was influenced by the factors like experience, training, job satisfaction, participation efficiency and achievement motivation. Performance effectiveness index of Andhra Pradesh extension professionals was influenced by the factors like experience, training, organizational commitment, innovation proneness and participation efficiency. The study also revealed that most of the farmers with respect to Kerala as well as Andhra Pradesh states, perceived that technology dissemination system of State Departments of Agriculture (SDA) was moderately favourable. Comparative analysis of farmers’ perception towards technology dissemination system of State Department of Agriculture (SDA) among Kerala and Andhra Pradesh states have shown that there was significant difference. The findings also demonstrated that most of the respondents with respect to Kerala as well as Andhra Pradesh states, belonged to middle age category, comprising medium experience; attended very high number of trainings. It was also found that most of the respondents from both states having normative commitment with no significant difference. Perceived workload, job satisfaction and decision making ability of the respondents from both states was medium with significant difference. Achievement motivation and innovation proneness of the respondents from both states was medium with no significant difference. Hence, the study assessed and compared the performance effectiveness of technology dissemination system of State Department of Agriculture (SDA) in Kerala and Andhra Pradesh by developing performance effectiveness index which also revealed that there was significant difference in their performance with clearly depicted constraints and suggestions from both the states.